OES characterization of streamers in a nanosecond pulsed SDBD using N2 and Ar transitions. (20th May 2016) - Goekce, S; Peschke, P; Hollenstein, Ch; Leyland, P; Ott, P
Abstract: The characterization of non-thermal homogeneous plasmas is possible using optical emission spectroscopy (OES), notably by estimating the reduced electric field. This method was applied to characterize streamers generated by a nanosecond pulsed surface dielectric barrier discharge (SDBD) operated in quiescent air at atmospheric pressure and also at 0.5 atm. The average reduced electric field associated with the surface streamers was determined using four different sets of transitions occurring in air plasmas, the first negative system (FNS) of N 2 +, the first positive system (FPS) and second positive system (SPS) of N 2 and argon transitions 2 p x − 1 s y . The analysis of the results allowed to critically assess the validity of the estimated reduced electric field for the present conditions. It is shown experimentally that the inhomogeneous nature of the streamer head influences significantly the estimation of the reduced electric field. Moreover, the estimated reduced electric field is not sufficient to characterize the processes taking place in the streamer head, due to the steep variation of both the reduced electric field E / N and the electron density n e in space and time. To overcome this limitation, a new method is proposed to take into account the spatial structure of a streamer head. The applicability of the new method is demonstrated for these experimental conditions and shows a very good agreement for the transitions tested.